PENGARUH LATAR BELAKANG PENDIDIKAN, LAMANYA BEKERJA, DAN KEMAMPUAN TEKNIK SISTEM INFORMASI AKUNTANSI APARATUR DESA TERHADAP PEMAHAMAN LAPORAN KEUANGAN DESA (Studi Empiris Desa Di Dua Kecamatan, Kabuaten Kubu Raya) - Lestari, Febryati Dwi (ABDI EQUATOR, 2025)
This research aims to analyze the influence of educational background, length of work, and the accounting information system technical capabilities of village officials on understanding village financial reports. Quality financial reports must be understandable, relevant, comparable and trustworthy. This research used primary data by distributing questionnaires to village officials in Sungai Ambawang District and Kuala Mandor B District, Kubu Raya Regency. Of the 80 questionnaires distributed, only 58 were returned, and 50 could be processed. The analysis technique used was multiple linear regression analysis which was processed with the help of the SPSS Version 26 program, where the data was previously tested for validity and reliability on the questionnaire data. Based on the analysis that has been carried out, it shows that using a partial regression test (T test), educational background and accounting information system technical abilities do not have a significant effect, while length of work has a significant effect on understanding financial reports. Meanwhile, using the simultaneous regression test (F Test), educational background, length of work, and accounting information system technical capabilities of Village Apparatus have a significant effect on understanding Village Financial Reports. The magnitude of the influence that occurs (Adjusted R2) by the three variables in this study together on the dependent variable is 57.2%, while the remaining 43% is influenced by other variables not examined in this study.